Oscillometry and computed tomography findings in patients with idiopathic pulmonary fibrosis. Issue 4 (14th December 2020) - Yamamoto, Yuji; Miki, Keisuke; Tsujino, Kazuyuki; Kuge, Tomoki; Okabe, Fukuko; Kawasaki, Takahiro; Matsuki, Takanori; Kagawa, Hiroyuki; Miki, Mari; Kida, Hiroshi
Although the utility of oscillometry for predicting disease severity in idiopathic pulmonary fibrosis (IPF) had been researched, little has been reported on the mechanism of why respiratory impedance reflects disease severity. In addition, traction bronchiectasis has been considered to reduce respiratory resistance and correlate negatively with airflow obstruction, but this hypothesis has not been validated. The present study aimed to investigate the correlations between oscillometric parameters and fibrosis-related lung abnormalities in IPF and to assess the utility of oscillometry as a surrogate marker for traction bronchiectasis and airflow obstruction. Eighty Japanese patients with IPF underwent high-resolution computed tomography (HRCT), spirometry, and oscillometry and were retrospectively investigated. Fibrosis-related HRCT findings were scored regarding airspace consolidation, honeycombing, architectural distortion, traction bronchiectasis, and fibrosis. Correlations between the HRCT scores, spirometric parameters, and oscillometric parameters were analysed. Respiratory reactance correlated positively with all fibrosis-related HRCT scores. Vital capacity and forced vital capacity (FVC) correlated negatively with oscillometric parameters and HRCT scores, reflecting the severity of restrictive ventilatory deficiency. Respiratory resistance was not related to any of the HRCT scores or forced expiratory volume in 1 s/FVC. However, forced expiratory volume in 1 s/FVC correlated positively with HRCT scores, which showed that airflow obstruction became milder as the disease progressed. In conclusion, respiratory reactance reflects fibrosis and restrictive ventilatory deficiency in IPF. Moreover, respiratory resistance is independent of traction bronchiectasis and airflow obstruction in patients with IPF, which implies that respiratory resistance might reflect different properties of the airways. Respiratory reactance measured by oscillometry correlates with fibrosis-related computed tomography findings in idiopathic pulmonary fibrosis (IPF). Respiratory resistance is independent of traction bronchiectasis and airflow obstruction in IPF. https://bit.ly/36zoGtf